Laparoscopic approach for huge benign ovarian cyst in woman with history of previous 5 laparotomies (including 4 cesarean section) - Taraby, Aisha Ebrahim; Zamreek, Ayman; Alyawer, Nahla; Alsudairy, Saad; Boogis, Dalal (Open Science Journal, 2020)
An adnexal mass (mass of the ovary, fallopian tube, or surrounding connective tissues) is a common gynecologic problem. In the United States, it is estimated that there is a 5 to 10% lifetime risk for women undergoing surgery for a suspected ovarian neoplasm. Adnexal masses may be found in females of all ages, from fetuses to older adults, and there are a wide variety of types of masses. Today, the surgical treatment has become more conservative and less invasive; hence, a laparoscopic approach in the presence of benign cysts has become a golden standard. In the past, patients with previous abdominal surgery were discouraged from undergoing laparoscopic surgery because of its increased risk of bowel injury caused by needle and trocar insertion. Complications occur two times more frequently in patients with previous laparotomy in a study of long series. The potential risk for injury of organs adherent to the abdominal wall during veress needle or trocar insertion as well as the necessity for adhesiolysis and its attendant complications are the two major specific problems constraining surgeons from performing laparoscopic cystectomy/ oophorectomy for patients with previous abdominal surgery. Herein, we report a case of a 32-year-old woman P4 + 2 with history of previous four cesarean section and a following laparotomy for interval sterilization presented to our clinic with abdominal mass, discovered by ultrasound scan, managed by a laparoscopic approach. Keywords: Benign ovarian cyst, laparoscopy, ovary, previous cesarean section, previous laparotomy